DIALEKTIKA LEADER-FOLLOWER YANG MEMECAHKAN KONSTRUK SOSIAL LEADERSHIP : Sebuah Pendekatan Otobiografi - Samuel Dimas Suryono; Artiawati Mawardi; Teguh Wijaya Mulya (CALYPTRA, 2018)
Leadership is widely researched phenomenon, yet least understandable. This phenomenon can’t be easily understand because most of leadership theory in the early research focuses on small portion of the whole leadership process itself. Seeing leader as sole constructor of leadership and ignoring follower in the process, is contributing wrong assumptions of leadership process. Therefore, through the analysis of leader-follower dialects that seen from social constructivism paradigm, I hope to remodel the social assumptions generated from early research. Through comparation of etymological analysis with early leadership research review, researcher will establish the boundaries between leadership and followership. This boundaries will be used to shape leader-follower dialects construct which then used further to analyze the dyadic level relations perceived by subjects. From this level analysis obtained that leader-follower dialects whil affect the quality of relations between leader and follower, thus affecting the whole efectivity of entire organization, therefore arguing that leader is not the most important factor in organization.